Case report: Illustrating associated malignancies in Paget’s disease using contrast-enhanced mammography - Mariano, Luciano; Nicosia, Luca; Bozzini, Anna; Pesapane, Filippo; Magnoni, Francesca; Mazzarol, Giovanni; Meneghetti, Lorenza; Sorce, Adriana; Cassano, Enrico (Frontiers in Oncology, 2025)
IntroductionThe following presentation explores the diagnostic potential of Contrast-Enhanced Mammography (CEM) in evaluating and managing Paget’s Disease (PD) of the breast, particularly as an alternative or complementary tool to Magnetic Resonance Imaging (MRI) in cases where MRI is contraindicated or inconclusive.Clinical casesTwo clinical cases of PD diagnosed at our Breast Imaging Division between January and May 2024 were analyzed using CEM. These cases involved imaging techniques, including Digital Mammography (DM), Breast Ultrasound (US), MRI and CEM, alongside histopathological confirmation through nipple-areolar complex (NAC) punch biopsies. CEM identified disease extensions and NAC involvement that was not evident in conventional imaging in both cases. CEM findings influenced surgical decisions, leading to total mastectomies with reconstruction instead of conservative approaches. The cases highlighted CEM’s sensitivity and ability to delineate the disease extent comparable to MRI.Discussion and conclusionsPD often presents diagnostic challenges due to frequent associations with underlying malignancies that are undetectable by standard imaging. While MRI is the gold standard, its limitations, such as costs, contraindications, and false positives, warrant alternative methods. CEM demonstrated utility in diagnosing and staging PD, offering benefits in patient acceptability, cost, and sensitivity comparable to MRI. CEM is a promising diagnostic and planning tool for PD management, especially in MRI-infeasible cases. More extensive multicentric studies will be needed to validate CEM’s role in this context. CEM could enhance PD diagnostic workflows and treatment strategies, significantly impacting clinical outcomes.